Constructing the true art market index: A novel 2-step hedonic approach and its application to the German art market - Roman Kräussl; Niels van Elsland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
This study develops a novel 2-step hedonic approach, which is used to construct a price index for German paintings. This approach enables the researcher to use every single auction record, instead of only those auction records that belong to a sub-sample of selected artists. This results in a substantially larger sample available for research and it lowers the selection bias that is inherent in the traditional hedonic and repeat sales methodologies. Using a unique sample of 61,135 auction records for German artworks created by 5,115 different artists over the period 1985 to 2007, we find that the geometric annual return on German art is just 3.8 percent, with a standard deviation of 17.87 percent. Although our results indicate that art underperforms the market portfolio and is not proportionally rewarded for downside risk, under some circumstances art should be included in an optimal portfolio for diversification purposes.
urn:nbn:de:hebis:30-54393
Keywords: G11; 330; Optimal Asset Allocation; Diversification; Art Investments; Hedonic Model; Downside Risk; Kunstgegenstand; Preisindex; Hedonischer Preis; Auktion; Kapitalertrag; Portfolio-Management; Deutschland